Action competence, Conflicting interests and Environmental education: The MUVIN Programme - Breiting, Søren; Hedegaard, Kristian; Mogensen, Finn; Nielsen, Kirsten; Schnack, Karsten (2015)
The present English edition is a full translation of the publication ‘Handlekompetence, interessekonflikter og miljøundervisning – MUVIN-projektet’ published in 1999 by Odense Universitetsforlag. Especially its focus on the development of students’ action competence makes this report a distinctive publication. But also its focus on societal issues and conflicting interests related to the use of natural resources contributes to its character The basic focus is on environmental education as education and as a contribution to a functioning democracy.